2012
DOI: 10.1111/j.1365-2966.2012.21309.x
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic bipolar wind in the interacting binary V 393 Scorpii

Abstract: V 393 Scorpii is a double periodic variable characterized by a relatively stable non‐orbital photometric cycle of 253 d. Mennickent et al. argue for the presence of a massive optically thick disc around the more massive B‐type component and describe the evolutionary stage of the system. In this paper, we analyse the behaviour of the main spectroscopic optical lines during the long non‐orbital photometric cycle. We study the radial velocity of the donor determining its orbital elements and find a small but sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…These components have been interpreted as absorption lines created at different density regions moving radially at distinct velocities (Danezis et al 2003). Mennickent et al (2012b) have interpreted DACs observed in the DPV system V393 Sco as signatures of a clumpy wind emerging from the disc in the direction of the binary motion. Interestingly, no DACs are observed at φ o = 0.84 (φ l = 0.76) and neither blue or red enhanced absorption wings.…”
Section: The O I 7773 Line and Dacsmentioning
confidence: 99%
See 1 more Smart Citation
“…These components have been interpreted as absorption lines created at different density regions moving radially at distinct velocities (Danezis et al 2003). Mennickent et al (2012b) have interpreted DACs observed in the DPV system V393 Sco as signatures of a clumpy wind emerging from the disc in the direction of the binary motion. Interestingly, no DACs are observed at φ o = 0.84 (φ l = 0.76) and neither blue or red enhanced absorption wings.…”
Section: The O I 7773 Line and Dacsmentioning
confidence: 99%
“…In the current scenario, the long-term periodicity is interpreted as cycles of mass loss from the binary into the interstellar medium. After a deep spectroscopic analysis of the DPV system V393 Sco, Mennickent et al (2012b) find that the long-term variability could be explained in terms of an anisotropic wind of variable strength whose emisivity is modulated with the long The reduced spectra are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/567/A140 cycle. However, the mechanism(s) involved in the wind strength variability are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The short-term variability corresponds to the orbital motion of the binary while the long-term variability A&A 552, A63 (2013) is still not completely understood. DPVs have been interpreted as semi-detached binaries showing cycles of mass loss into the interstellar medium (Mennickent et al 2008(Mennickent et al , 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…We find that HD 170882 shows spectroscopic properties similar to other DPVs like AU Monocerotis, V 393 Scorpii, DQ Velorum and OGLE 05155332-6925581 (Mennickent et al, 2008, 2012a, 2012b, Barría et al 2013, Garrido et al 2013. These properties include the existence of an optically thick disc surrounding a B-type star and evidence for stream-disc interaction.…”
Section: Discussionmentioning
confidence: 62%
“…The system is characterized by a long photometric cycle of 536 days and is the third longest-period member of the Galactic Double Period Variables (DPVs), after V 495 Cen and V 4142 Sgr (Mennickent & Rosales 2014, Mennickent et al 2012a. DPVs are intermediate mass interacting binaries showing a long photometric cycle lasting about 33 times the orbital pe-riod, which has been interpreted as cyclic episodes of mass loss (Mennickent et al 2003, Mennickent et al 2008, 2012b, Poleski et al 2010). More than 200 DPVs have been found in the Galaxy and the Magellanic Clouds (Mennickent 2013), but very few of them have been studied spectroscopically (e.g.…”
Section: Introductionmentioning
confidence: 99%